ANALYSIS OF FIGURATIVE LANGUAGE IN TAYLOR SWIFT SELECTED SONGS IN “MIDNIGHT “ALBUM AND ITS CONTRIBUTION TO ENGLISH TEACHING AT SENIOR HIGH SCHOOL - Dodi Widia Nanda; Martiya Nurni Khairita; Silvi Revina (Jurnal Tunas Pendidikan, 2023)
This study aims to analyzed of Figurative Language Used in selected Taylor Swift songs in the midnight album and its Contribution to English Teaching in Senior High School". The figurative language found in Taylor Swift's songs is analyzed into three types, meanings, and their contribution to English teaching. The writer used Abbrams' theory (1999) as an indicator in this study and SLA theory applied as the second theoretical for this study regarding to the beneficial and contribution of song lyrics for English teaching in teaching English as foreign language. In this study, the writer used a qualitative method. The author focuses on five types of figurative language analysis, namely hyperbole, metaphor, simile, irony, and personification. The research data were obtained from five songs in Taylor Swift's "midnight" album. The songs are "snow on the beach", "anti hero", "you're on your own kid", "bigger than the whole sky", "high infidelity". After analyzing the data, the writer found twenty-eight figurative language expressions, including thirteen hyperboles, eight metaphors, three similes, two ironies, and two personifications. Hyperbole is the most used figurative language in in selected Taylor Swift songs in the midnight album. In addition, this research contributes to the teaching of English. The data found that this research contributes to the teaching of English